In the mood to buy? Understanding the interplay of mood regulation and congruence in an international context - (:unkn) unknown (SPRINGER, 2012)
Literature reports different effects of mood on measures of consumer behavior. Either mood congruence or mood regulation theories serve to explain these effects, though the latter theory is perhaps more sophisticated. This research goes a step further: in a sequence of four studies, the authors consider different products (with and without mood-lifting capabilities) and consumers' beliefs in the transience of their mood to illuminate the interplay between the two theoretical approaches. Culture (individualism vs. collectivism) emerges as an important driver of mood transience. Mood transience drives the likelihood of mood regulation through the consumption of products with mood-lifting capabilities. Willingness to pay serves as the dependent variable, in contrast with mood research that has focused almost entirely on nonmonetary forms of consumer behavior. Greater willingness to pay variance in bad moods, compared with good moods, offers evidence of the opposing effects of mood congruence and regulation.
Keywords: Mood; Mood regulation theory; Mood congruence theory; Mood transience; Willingness to pay; WILLINGNESS-TO-PAY; SELF; BEHAVIOR; CONSEQUENCES; CONSUMPTION; EXPERIENCE; FAILURE; AMERICA; SEARCH; POWER